Westonci.ca makes finding answers easy, with a community of experts ready to provide you with the information you seek. Experience the ease of finding quick and accurate answers to your questions from professionals on our platform. Discover detailed answers to your questions from a wide network of experts on our comprehensive Q&A platform.
Sagot :
the easiest way to solve that would be elimination method, but if you have to do substitution:
x-9=-3
add 9 to each side to get
x=6
then plug 6 into the other equation for x
2(6)-y=23
and solve for y :)
x-9=-3
add 9 to each side to get
x=6
then plug 6 into the other equation for x
2(6)-y=23
and solve for y :)
2x - y = 23
x - 9 = -3
x - 9 = -3
+ 9 + 9
x = 6
2(6) - y = 23
12 - y = 23
- 12 - 12
-y = 11
y = -11
(x, y) = (6, -11)
x - 9 = -3
x - 9 = -3
+ 9 + 9
x = 6
2(6) - y = 23
12 - y = 23
- 12 - 12
-y = 11
y = -11
(x, y) = (6, -11)
Thank you for visiting. Our goal is to provide the most accurate answers for all your informational needs. Come back soon. Thanks for using our service. We're always here to provide accurate and up-to-date answers to all your queries. Your questions are important to us at Westonci.ca. Visit again for expert answers and reliable information.